EKONOMI SYARIAH DALAM AL-QUR’AN (STUDI TAFSIR MAUDHU'I AYAT-AYAT PRODUKSI, DISTRIBUSI DAN KONSUMSI) - Mubarok; Misno; Chaniago, Asdi (ALAMIAH : Jurnal Muamalah dan Ekonomi Syariah, 2024)
The research method used is the maudhu'i interpretation approach, data obtained through the collection of verses related to production, distribution and consumption. Then the verses are analyzed with the approach of classical and contemporary interpretation methods so as to produce meanings and correlations of these verses. This research shows that there are many verses related to economic activities, especially in the fields of production, distribution and consumption in the Qur'an. The verses related to production include; regarding the iron, steel and brass industry (QS. Saba': 10-11, Al-Kahf: 96), the gold, silver, pearl and silk jewelry industry (QS Al-Insan: 15-16, Al-Hajj, Al-Kahf : 31), the oil and mining industry (QS Al-Mu'minun: 20, Al-Hadid: 25), the leather, textile and glass industry (QS.Al-Nahl: 80, An-Naml: 44), the ceramics industry, bricks and buildings (QS Al-Qashah: 38, Al-Mukmin: 36-37) etc., and the shipping industry (QS Hud: 37,38, 42, QS Al-Qamar: 13-14). The verses related to distribution are; QS. Al-Hasyr: 7, At-Taubah: 103. Verses about consumption namely; QS. Al-Baqarah (2): 168, 172 QS. Al-Maidah: 4, 88 QS. Al-An'am: 118, 141-142 QS. Al-A'raaf: 31, 160 QS. al-Isra: 26-28 QS. at-Thur (52): 19 QS. al-Haqqah (69): 24 QS. Al-Mursalah: 43 QS. an-Nahl: 114 QS. Thaha (20): 54, 81 QS. al-Hajj: 28, 36 QS. al-Mukminun (23): 51 QS. Saba (34): 15 QS. Al-Mursalah: 46. Production in the Qur'an should be optimal in working, istiqamah, not doing damage, and placing the concept of benefit as a production orientation. Consumption which is the next part of economic activity should be frugal in using assets, spending assets in a lawful manner, and running the economic chain in a lawful way.